Sequence based analysis of carbohydrate transporters of Saprophytic fungi and mycorrhizal fungi - RICHA ANAND, (International Journal of Pharma and Bio Sciences, 2017)
Arbuscular mycorrhizal fungi (AMF) forming symbiotic association with plant roots facilitate the uptake of soil nutrients and in exchange obtain carbohydrates, thus representing a large sink for atmospheric plant fixed CO2. Characterization of the first known glomeromycotan monosaccharide transporter, GpMST1, by exploiting the unique symbiosis of a glomeromycotan fungus (Geosiphon pyriformis) with cyanobacteria has been worked out. The GpMST1 gene has a very low GC content and contains six introns with unusual boundaries. Characterization of a new transporter family involved in fungal symbiosis has lead to a better understanding of carbon flows in terrestrial environments. Saprophytic fungi are the largest group of fungi, growing on dead organic matter of plants and animals. Saprophytic fungi play an important role in decomposition of organic matters and nutrient cycling. AMFs and saprophytic fungi are involved in different ecological functions. An In-silico study was therefore performed to identify the homology between monosaccharide transporter GpMST1 and the carbohydrate transporters present in saprophytic fungi and to trace out the phylogenetic relations. During the study different proteins belonging to 10 saprophytic fungi showed homology with GpMST1 carbon transporter of AMF.